Factors related to the application of artificial intelligence technology in teaching and learning management by private vocational education teachers in Bangkok - Thitawannonate, Kaimug (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to: 1) examine private vocational education teachers’ digital technology understanding, attitudes toward the use of Artificial Intelligence in teaching, administrative and institutional support, access to resources and infrastructure, teacher training and development, and the application of AI in teaching; and 2) investigate the relationships between these factors and the application of AI in teaching among private vocational education teachers in Bangkok. This quantitative research employed a multi-stage sampling procedure to recruit a sample of 346 private vocational education teachers in Bangkok. The research instrument was a five-point Likert rating scale questionnaire. Data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation, as well as inferential statistics comprising Pearson’s product-moment correlation coefficient. The research findings revealed that the overall application of Artificial Intelligence (AI) technology in teaching and learning management among private vocational education teachers in Bangkok was at a good level. A detailed examination indicated that all factor variables had mean scores at a good level, ranked from highest to lowest as follows: attitude toward the use of AI in teaching had the highest mean, followed by administrative and institutional support, digital technology understanding, teacher training and development, and access to resources and infrastructure had the lowest mean. All factor variables exhibited a positive relationship with the application of AI in teaching among private vocational education teachers in Bangkok at a moderate to high level, with statistical significance at the .01 level. The factor of teacher training and development had the highest positive relationship. For practical recommendations, educational institutions should prioritize the design and implementation of systematic and continuous teacher training and development programs to enhance teachers’ skills and confidence in applying AI in teaching and learning management effectively.